2022
DOI: 10.3390/agronomy12071560
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Mitigated Yield-Scaled N2O and NO Emissions and Ensured Vegetable Quality and Soil Fertility: A 3-Year Greenhouse Field Observation

Abstract: Biochar amendments have been widely used in agricultural soil for lowering N2O and NO emissions while improving soil fertility and crop performance. However, a thorough understanding of the longevity of the favorable effects would be a prerequisite for large-scale biochar application in agriculture. We conducted a three-year greenhouse vegetable trial in Southeast China to systematically investigate the impacts of biochar mixed with nitrogen (N) on soil N2O and NO emissions, vegetable performance, and soil fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(126 reference statements)
0
0
0
Order By: Relevance
“…However, the long-term residual effects of biochar are still unknown, partly due to the lack of appropriate field experiments [27]. The current literature has shown that application of biochar has the potential to reduce soil N 2 O emissions [15,[28][29][30][31][32]. However, other studies have found transient or no discernible effects [28,33,34], or even occasional increases in N 2 O emissions [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…However, the long-term residual effects of biochar are still unknown, partly due to the lack of appropriate field experiments [27]. The current literature has shown that application of biochar has the potential to reduce soil N 2 O emissions [15,[28][29][30][31][32]. However, other studies have found transient or no discernible effects [28,33,34], or even occasional increases in N 2 O emissions [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Soil N 2 O is primarily produced via microbial processes such as nitrification and denitrification [4]. It is well documented that soil aeration, the availability of N substrates, and soil organic carbon (SOC) content are among the most robust controllers of N 2 O fluxes from various agroecosystems [5][6][7][8]. These factors are closely related to climate (e.g., temperature and precipitation), soil properties (e.g., soil pH, texture, and organic matter content), and field management practices (e.g., N input rate, organic amendments, and tillage), thus leading to the large spatial and temporal variations in N 2 O emissions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%